Enhancing Students' Higher-Order Thinking Skills Through Accounting Game-Based Learning: A Development and Evaluation Study - Nurdian Susilowati; Amir Mahmud; Ida Nur Aeni; Puji Novita Sari (Universitas Pendidikan Ganesha, 2025)
The low ability of students to understand the journal material is adjustment, which requires high-level thinking skills (HOTS). Based on the results of the initial survey, as many as 88% of students stated that adjustment journals are very difficult to understand, and conventional media such as PowerPoint and videos have not been able to improve students' learning outcomes and analytical skills. Therefore, this study aims to design, develop, and test the effectiveness of an educational game-based learning media called Edu-Adjustment Journal to improve students' HOTS abilities in adjustment journal materials. The subjects of the study were 48 grade XII students at one of the public high schools in Semarang who were divided into two groups, namely the experimental group using the Edu-Adjustment Journal and the control group using PowerPoint media. This research uses a Research and Development (R&D) approach with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. Data collection techniques include observation, questionnaires, and documentation to assess the feasibility, attractiveness, and effectiveness of learning media. The data was analyzed quantitatively using validity, reliability, difficulty analysis of question items, and independent sample t-test, and qualitatively through reduction, classification, and data presentation. The results showed that all instruments were valid and reliable with an average validation value of 92%, and there was a significant difference between the experimental and control groups with a significance value of p = 0.004. The average learning outcomes of students who use Edu-Adjustment Journal (78.42) are higher than students who use PowerPoint (71.08). Thus, the Edu-Adjustment Journal learning media has proven to be effective in improving students' high-level thinking skills, motivation, and understanding of adjustment journal materials.